Document retrieval from a citation database using conceptual clustering and co-word analysis. - Hui SC; Fong ACM (Online Information Review, 2004)
Traditional document retrieval techniques are ineffective in finding relevant documents due to a lack of semantic understanding of relevance. In this article, two techniques are described - conceptual clustering and co-word analysis - aimed at injecting intelligence into the retrieval of documents stored in a citation database. Performance analysis has revealed that these techniques are better than traditional lexical analysis in terms of retrieval speed and accuracy.